Participatory Spaces Under Urban Capitalism Contesting the Boundaries of Democratic Practices - Holdo, Markus (Routledge Research in Planning and Urban Design, 2024)
Can people use new participatory spaces to reclaim their rights as citizens and challenge structures of political power? This book carefully examines the constraints and possibilities for participatory governance under capitalism. To understand what is at stake in the politics of participation, we need to look beyond the values commonly associated with it. Citizens face a dilemma: should they participate, even if this helps to sustain an unjust system, or not participate, thereby turning down rare opportunities to make a difference? By examining the rationale behind democratic innovation and the reasons people have for getting involved, this book provides a theory of how citizens can use new democratic spaces to challenge political boundaries. Connecting numerous international case studies and presenting original research from Rosario, Argentina, this book offers a crucial corrective to previous research. What matters most is not the design of new models of participation nor is it the supposed radical imagination of political leaders. It is whether people use new spaces for participation to renegotiate what democracy means in practice. Bridging critical urban studies and democratic theory, this book will be of interest to researchers and students in the fields of democratic innovations, political economy and urban planning. It will also provide activists and practitioners of participatory democracy with important tools to expand spaces of grassroots democracy.